2020
DOI: 10.1371/journal.pone.0232897
|View full text |Cite
|
Sign up to set email alerts
|

Social approach and place aversion in relation to conspecific pain in dairy calves

Abstract: Despite scientific interest in animal empathy, and growing public concern for farm animal welfare, the empathic abilities of farm animals remain under researched. In this study, we investigated empathic responses of young Holstein dairy calves to conspecifics recovering from hot-iron disbudding, a painful procedure common on dairy farms. A combination of social approach and place conditioning was used. First, 'observer' calves witnessed two 'demonstrator' calves recover from either a painful procedure (hot-iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(46 reference statements)
0
6
1
Order By: Relevance
“…In some species (e.g., rats), tactile contact is an important cue for inducing social buffering 60 , and thus we could expect that positive social interactions occur more frequently after experiencing stress to allow transmission of social buffering. Our results are in contrast with findings of Ede et al who reported that calves spent more time in proximity to a conspecific in pain 47 , and Gingerich et al who even reported decreased interest of disbudded calves in sharing shelter with other calves 6 . Our results are consistent with the findings of Turner et al who did not confirm increased maternal care towards calves displaying the most behavioral evidence of pain 48 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In some species (e.g., rats), tactile contact is an important cue for inducing social buffering 60 , and thus we could expect that positive social interactions occur more frequently after experiencing stress to allow transmission of social buffering. Our results are in contrast with findings of Ede et al who reported that calves spent more time in proximity to a conspecific in pain 47 , and Gingerich et al who even reported decreased interest of disbudded calves in sharing shelter with other calves 6 . Our results are consistent with the findings of Turner et al who did not confirm increased maternal care towards calves displaying the most behavioral evidence of pain 48 .…”
Section: Discussioncontrasting
confidence: 99%
“…Research on transmission of social buffering in cattle is rare, and the findings are not consistent. Ede et al reported that calves spent more time in proximity and paid more attention to a conspecific in pain compared to a sham treated calf 47 . However, Gingerich et al reported that disbudded calves left shelter more frequently when it was occupied 6 , and Turner et al reported that ear tagging and castration did not result in calves receiving more maternal attention 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Grandin et al (1994) [ 74 ] demonstrates that it is difficult for cattle to unpair negative experiences in a given location despite other experiences that may follow, which is especially notable on rangelands where there are infrequent handling opportunities. In addition to memory of past experiences causing fear and stress in processing environments [ 71 , 72 , 75 , 76 , 77 ], immediate procedures surrounding human-animal interaction research may also impact outcome measures. For example, if a study is using chute score and flight speed to measure fear of restraint by humans during or after some aversive or painful experience (e.g., branding), it would be difficult to disentangle fear of handling from expression of pain or anxiety caused by the procedure itself or from the sounds and stress hormones of other cattle that have been processed prior to the focal cow [ 78 , 79 , 80 , 81 ].…”
Section: Considerations and Limitations Of Hai Research In Rangelamentioning
confidence: 99%
“…Furthermore, it seems to be to the contrast with results of Ede et al (2020) who found that calves spent more time in proximity and paid more attention to a conspeci c in pain compared to a sham treated calf. However, the authors also found that physical contact occurred infrequently among calves 39 . Gingerich et al (2020) found that disbudded calves left shelter more frequently when it was occupied 9 and Dunlap et al…”
Section: Discussionmentioning
confidence: 92%